Flame-retardant PVC (polyvinyl chloride) sleeve and preparation method thereof
By adopting internal and external tube structures and metal copper mesh coating technology in PVC casing, combining active nano calcium carbonate and activated fibers, the shortcomings of PVC casing in compressive resistance, thermal stability and flame retardant properties are solved, and high efficiency is achieved The flame retardant and thermal conductivity are improved, reducing the risk of heavy metal pollution.
Patent Information
- Application Number
- CN202411454219.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Existing PVC sleeves have shortcomings in compression resistance, thermal stability and flame retardant properties, especially the irregular block particles of calcium carbonate lead to poor mechanical properties, and the commonly used stabilizers contain heavy metals, which poses a risk of environmental pollution.
Adopt the inner and outer tube structure, the inner tube is coated with metal copper mesh, and active nano calcium carbonate, activated fibers, flame retardant and calcium-zinc stabilizer are added to the inner and outer tubes to improve the compressive, thermal and flame retardant properties of the material through injection molding process. .
It significantly improves the impact resistance, thermal stability and flame retardant properties of PVC casing, reduces the risk of heavy metal pollution, and is suitable for large-scale promotion and application.
Smart Images

Figure CN119283450A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyvinyl chloride casings, and in particular to a flame-retardant PVC casing and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the most widely used general-purpose plastics. Pipes made of it have the advantages of smooth pipe wall, low resistance and low price. PVC plastic not only has excellent mechanical properties, but also has excellent electrical insulation properties, so it has a great advantage in the casing industry.
[0003] When PVC pipe is used as cable sheath, multiple cables are wrapped inside it. In order to ensure that the cable sheath has good supporting and protective performance, various fillers are often added to modify the PVC pipe to increase the rigidity of the PVC pipe. Currently, calcium carbonate is added as a conventional inorganic filler for pipes to enhance the mechanical properties of the sheath. However, the particle morphology of calcium carbonate is irregular block. After mixing with PVC resin, a large number of gaps are generated between the particles, which are easily broken by external impact.
[0004] At the same time, the cable will have heating problems during operation. Since ordinary PVC has poor thermal stability, it will begin to decompose when the temperature exceeds 90℃, and will obviously decompose when the temperature is higher than 120℃. When burning, it will release a large amount of hydrogen chloride gas, thus causing "secondary disasters" after the fire, seriously affecting the evacuation of personnel and the development of fire rescue work. Currently, commonly used stabilizers include lead salts, chromium salts, etc., but they contain heavy metals that will cause serious pollution to the environment. Calcium zinc stabilizer is recognized as a non-toxic compound, but its thermal stability effect is worse than that of lead salts.
[0005] Therefore, developing a PVC casing with excellent compressive resistance, good thermal stability, excellent flame retardant properties, and easy promotion and application has important research significance and application value. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a flame retardant PVC sleeve and a preparation method thereof.
[0007] A flame-retardant PVC sleeve comprises: an inner tube, a metal copper mesh coated on the outer side of the inner tube, and an outer tube coated on the metal copper mesh and the outer side of the inner tube by injection molding; the raw materials of the inner tube comprise, by mass, 80-150 parts of polyvinyl chloride, 1-3 parts of chlorinated polyethylene, 20-40 parts of active nano calcium carbonate, 1-2 parts of paraffin wax, 1-2 parts of stearic acid, 1-3 parts of flame retardant, and 1-2 parts of calcium zinc stabilizer; the raw materials of the outer tube comprise, by mass, 50-120 parts of polyvinyl chloride, 1-5 parts of activated fiber, 10-20 parts of active nano calcium carbonate, 1-2 parts of zeolite powder, 1-2 parts of magnesium oxide, 1-2 parts of paraffin wax, 1-2 parts of polyethylene wax, 1-2 parts of stearic acid, 1-5 parts of flame retardant, 1-3 parts of calcium zinc stabilizer, and 1-2 parts of processing aid LPA40.
[0008] Preferably, the flame retardant is at least one of zinc borate, zinc stannate, ammonium octamolybdate, and ammonium polyphosphate.
[0009] Preferably, the active nano calcium carbonate is prepared by the following steps: adding calcium hydroxide to water and stirring for 10-20 minutes, adding yttrium oxide under stirring, introducing carbon dioxide gas into the water under stirring, and spray drying; adding to dioxane, and then adding polylactic acid, stirring at 80-95° C. for 10-30 minutes, removing the solvent under reduced pressure, continuing to stir at 120-130° C. for 5-10 minutes, cooling to room temperature, and crushing.
[0010] Preferably, the mass ratio of calcium hydroxide, yttrium oxide and polylactic acid is 5-10:0.01-0.1:0.1-1.
[0011] Preferably, the activated fibers have a diameter of 0.1-0.3 mm and a length of 3-5 mm.
[0012] Preferably, the activated fiber is prepared by the following steps: adding lignin to deionized water and stirring evenly, adding sodium silicate, sodium alginate and graphene oxide thereto under stirring, stirring at 80-95° C. for 10-30 min, adjusting the pH value of the system to 2-3, rotary drying, and melt spinning.
[0013] Preferably, the mass ratio of lignin, sodium silicate, sodium alginate and graphene oxide is 5-10:1-2:1-2:1-3.
[0014] Preferably, the spinning temperature is 200-220°C.
[0015] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Mix polyvinyl chloride and activated fiber, stir at 100-140°C for 10-30min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, flame retardant, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 5-15min, extrude at 180-200°C, and pelletize to obtain outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at 100-140°C for 10-30min, adding active nano calcium carbonate, paraffin, stearic acid, flame retardant, calcium zinc stabilizer in sequence, mixing evenly, extruding at 180-200°C, and pelletizing to obtain inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0016] Beneficial effects: The present invention adopts calcium-zinc composite stabilized lubricant to replace the traditional lead salt stabilizer, and cooperates with the flame retardant. The system has excellent flame retardant performance and high oxygen index, and is suitable for large-scale promotion and application.
[0017] The present invention combines graphene oxide in the lignin matrix, and then the activated fiber obtained after spinning not only has good affinity with polyvinyl chloride, but also effectively improves the thermal conductivity of the outer tube on the basis of ensuring the mechanical strength of the product, and cooperates with the metal copper mesh to quickly transfer the heat of the cable to the external environment, so that the heat will not accumulate on the inner tube that is in direct contact with the cable, effectively ensuring the normal operation of the cable. At the same time, polyvinyl chloride and activated fiber are compounded, and the two have high bonding strength. Further combined with active nano calcium carbonate, not only can good support and excellent thermal stability be provided for the casing, the system has high impact resistance, and excellent flame retardant performance.
[0018] The present invention adds calcium hydroxide to water to form a suspension, adds yttrium oxide and forms yttrium-doped nano calcium carbonate particles after carbon dioxide treatment, and then combines polylactic acid on the surface, which can significantly increase the dispersibility and stability of calcium carbonate, and has high interfacial compatibility with polyvinyl chloride substrates, significantly improving the mechanical properties of the material. It was found through experiments that the active nano calcium carbonate and the flame retardant are compounded with significant synergistic effects, which can not only ensure the impact strength of the material, but also greatly enhance the flame retardant effect and have significant smoke suppression effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a comparison chart of the tensile strength and bending strength of the flame-retardant PVC sleeves obtained in Example 5 and Comparative Examples 1-2.
[0020] Figure 2 It is a comparison chart of the impact strength and oxygen index of the flame-retardant PVC sleeves obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0021] The present invention will be further explained below in conjunction with specific embodiments.
[0022] The calcium zinc stabilizer was purchased from Dongguan Yu Chemical Co., Ltd., model CZ-108. The processing aid LPA40 was purchased from Shandong Ruimou Polymer Materials Co., Ltd. Example 1 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0023] The raw materials of the inner tube include: 80kg of polyvinyl chloride, 1kg of chlorinated polyethylene, 20kg of active nano calcium carbonate, 1kg of paraffin, 1kg of stearic acid, 1kg of zinc borate, and 1kg of calcium zinc stabilizer.
[0024] The raw materials of the outer tube include: 50kg of polyvinyl chloride, 1kg of activated fiber with a diameter of 0.1mm and a length of 3mm, 10kg of active nano calcium carbonate, 1kg of zeolite powder, 1kg of magnesium oxide, 1kg of paraffin, 1kg of polyethylene wax, 1kg of stearic acid, 1kg of zinc borate, 1kg of calcium zinc stabilizer, and 1kg of processing aid LPA40.
[0025] The active nano calcium carbonate is prepared by the following steps: 5 kg of calcium hydroxide is added to 50 kg of water, stirred at a speed of 1000 r / min for 10 minutes, 0.01 kg of yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 7 L / min, the introduction time is 25 seconds, and spray drying is performed; the water is added to 10 kg of dioxane, 0.1 kg of polylactic acid is added, stirred at a temperature of 80° C. for 10 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 120° C. for 5 minutes, cooled to room temperature, and crushed.
[0026] The activated fiber is prepared by the following steps: add 5 kg of lignin to 20 kg of deionized water and stir evenly, add 1 kg of sodium silicate, 1 kg of sodium alginate and 1 kg of graphene oxide under stirring, stir at 80 ° C for 10 minutes, adjust the pH value of the system to 2-3 with hydrochloric acid, remove the deionized water by rotary evaporation, and melt-spin after drying at a spinning temperature of 200 ° C.
[0027] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 100°C for 10 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, zinc borate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 5 min, extrude at 180°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 100°C for 10 minutes, adding active nano calcium carbonate, paraffin, stearic acid, zinc borate, and calcium zinc stabilizer in sequence and mixing evenly, extruding at a temperature of 180°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0028] Example 2 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0029] The raw materials of the inner tube include: 150kg of polyvinyl chloride, 3kg of chlorinated polyethylene, 40kg of active nano calcium carbonate, 2kg of paraffin, 2kg of stearic acid, 3kg of zinc stannate, and 2kg of calcium zinc stabilizer.
[0030] The raw materials of the outer tube include: 120kg polyvinyl chloride, 5kg activated fiber with a diameter of 0.3mm and a length of 5mm, 20kg active nano calcium carbonate, 2kg zeolite powder, 2kg magnesium oxide, 2kg paraffin, 2kg polyethylene wax, 2kg stearic acid, 5kg zinc stannate, 3kg calcium zinc stabilizer, and 2kg processing aid LPA40.
[0031] The active nano calcium carbonate is prepared by the following steps: 10 kg of calcium hydroxide is added to 100 kg of water, stirred at a speed of 2000 r / min for 20 minutes, 0.1 kg of yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 6 L / min, the introduction time is 30 seconds, and spray drying is performed; the water is added to 20 kg of dioxane, 1 kg of polylactic acid is added, stirred at a temperature of 95° C. for 30 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 130° C. for 10 minutes, cooled to room temperature, and crushed.
[0032] The activated fiber is prepared by the following steps: 10 kg of lignin is added to 30 kg of deionized water and stirred evenly, 2 kg of sodium silicate, 2 kg of sodium alginate and 3 kg of graphene oxide are added thereto under stirring, and stirred at 95 ° C for 30 minutes, and the pH value of the system is adjusted to 2-3 with hydrochloric acid, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 220 ° C.
[0033] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 140°C for 30 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, zinc stannate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 15 min, extrude at 200°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 140°C for 30 minutes, adding active nano calcium carbonate, paraffin, stearic acid, zinc stannate, and calcium zinc stabilizer in sequence and mixing evenly, extruding at a temperature of 200°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0034] Example 3 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0035] The raw materials of the inner tube include: 100kg of polyvinyl chloride, 2.5kg of chlorinated polyethylene, 25kg of active nano calcium carbonate, 1.7kg of paraffin, 1.2kg of stearic acid, 2.5kg of ammonium octamolybdate, and 1.3kg of calcium zinc stabilizer.
[0036] The raw materials of the outer tube include: 100kg of polyvinyl chloride, 4kg of activated fiber with a diameter of 0.15mm and a length of 4.5mm, 12kg of active nano calcium carbonate, 1.7kg of zeolite powder, 1.2kg of magnesium oxide, 1.7kg of paraffin, 1.2kg of polyethylene wax, 1.7kg of stearic acid, 2kg of ammonium polyphosphate, 2.5kg of calcium zinc stabilizer, and 1.3kg of processing aid LPA40.
[0037] The active nano calcium carbonate is prepared by the following steps: 9 kg calcium hydroxide is added to 70 kg water, stirred at a speed of 1800 r / min for 13 min, 0.07 kg yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 10 L / min, the introduction time is 40 s, and spray drying is performed; the water is added to 12 kg dioxane, 0.7 kg polylactic acid is added, stirred at a temperature of 85° C. for 25 min, the solvent is removed under reduced pressure, stirring is continued at a temperature of 122° C. for 9 min, cooled to room temperature, and crushed.
[0038] The activated fiber is prepared by the following steps: 7 kg of lignin is added to 28 kg of deionized water and stirred evenly, 1.3 kg of sodium silicate, 1.8 kg of sodium alginate and 1.5 kg of graphene oxide are added thereto under stirring, stirred at 90 ° C for 15 minutes, the pH value of the system is adjusted to 2-3 with hydrochloric acid, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 215 ° C.
[0039] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 110°C for 25 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, ammonium polyphosphate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 8 min, extrude at 195°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 110°C for 25 minutes, adding active nano calcium carbonate, paraffin, stearic acid, ammonium octamolybdate, and calcium zinc stabilizer in sequence, mixing evenly, extruding at a temperature of 185°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0040] Example 4 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0041] The raw materials of the inner tube include: 130kg of polyvinyl chloride, 1.5kg of chlorinated polyethylene, 35kg of active nano calcium carbonate, 1.3kg of paraffin, 1.8kg of stearic acid, 1.5kg of ammonium polyphosphate, and 1.7kg of calcium zinc stabilizer.
[0042] The raw materials of the outer tube include: 60kg of polyvinyl chloride, 2kg of activated fiber with a diameter of 0.25mm and a length of 3.5mm, 18kg of active nano calcium carbonate, 1.3kg of zeolite powder, 1.8kg of magnesium oxide, 1.3kg of paraffin, 1.8kg of polyethylene wax, 1.3kg of stearic acid, 4kg of ammonium polyphosphate, 1.5kg of calcium zinc stabilizer, and 1.7kg of processing aid LPA40.
[0043] The active nano calcium carbonate is prepared by the following steps: 7 kg calcium hydroxide is added to 90 kg water, stirred at a speed of 1200 r / min for 17 minutes, 0.03 kg yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 5 L / min, the introduction time is 10 seconds, and spray drying is performed; the water is added to 18 kg dioxane, 0.3 kg polylactic acid is added, stirred at a temperature of 90° C. for 15 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 128° C. for 7 minutes, cooled to room temperature, and crushed.
[0044] The activated fiber is prepared by the following steps: 9 kg of lignin is added to 22 kg of deionized water and stirred evenly, 1.7 kg of sodium silicate, 1.2 kg of sodium alginate and 2.5 kg of graphene oxide are added thereto under stirring, stirred at 85 ° C for 25 minutes, the pH value of the system is adjusted to 2-3 with hydrochloric acid, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 205 ° C.
[0045] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 130°C for 15 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, ammonium polyphosphate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 12 min, extrude at 185°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 130°C for 15 minutes, adding active nano calcium carbonate, paraffin, stearic acid, ammonium polyphosphate, and calcium zinc stabilizer in sequence, mixing evenly, extruding at a temperature of 195°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0046] Example 5 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0047] The raw materials of the inner tube include: 120kg of polyvinyl chloride, 2kg of chlorinated polyethylene, 30kg of active nano calcium carbonate, 1.5kg of paraffin, 1.5kg of stearic acid, 2kg of ammonium polyphosphate, and 1.5kg of calcium zinc stabilizer.
[0048] The raw materials of the outer tube include: 80kg of polyvinyl chloride, 3kg of activated fiber with a diameter of 0.2mm and a length of 4mm, 15kg of active nano calcium carbonate, 1.5kg of zeolite powder, 1.5kg of magnesium oxide, 1.5kg of paraffin, 1.5kg of polyethylene wax, 1.5kg of stearic acid, 3kg of zinc borate, 2kg of calcium zinc stabilizer, and 1.5kg of processing aid LPA40.
[0049] The active nano calcium carbonate is prepared by the following steps: 8 kg of calcium hydroxide is added to 80 kg of water, stirred at a speed of 1500 r / min for 15 minutes, 0.05 kg of yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 10 L / min, the introduction time is 15 seconds, and spray drying is performed; the water is added to 15 kg of dioxane, 0.5 kg of polylactic acid is added, stirred at a temperature of 88° C. for 20 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 125° C. for 8 minutes, cooled to room temperature, and crushed.
[0050] The activated fiber is prepared by the following steps: 8 kg of lignin is added to 25 kg of deionized water and stirred evenly, 1.5 kg of sodium silicate, 1.5 kg of sodium alginate and 2 kg of graphene oxide are added thereto under stirring, stirred at 88 ° C for 20 minutes, the pH value of the system is adjusted to 2-3 with hydrochloric acid, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 210 ° C.
[0051] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 150°C for 20 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, zinc borate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 10 min, extrude at 190°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 120°C for 20 minutes, adding active nano calcium carbonate, paraffin, stearic acid, ammonium polyphosphate, and calcium zinc stabilizer in sequence, mixing evenly, extruding at a temperature of 190°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0052] Comparative Example 1 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0053] The raw materials of the inner tube include: 120kg of polyvinyl chloride, 2kg of chlorinated polyethylene, 30kg of active nano calcium carbonate, 1.5kg of paraffin, 1.5kg of stearic acid, 2kg of ammonium polyphosphate, and 1.5kg of calcium zinc stabilizer.
[0054] The raw materials of the outer tube include: 80kg of polyvinyl chloride, 2.54kg of activated fiber with a diameter of 0.2mm and a length of 4mm, 0.46kg of graphene oxide, 15kg of active nano-calcium carbonate, 1.5kg of zeolite powder, 1.5kg of magnesium oxide, 1.5kg of paraffin, 1.5kg of polyethylene wax, 1.5kg of stearic acid, 3kg of zinc borate, 2kg of calcium zinc stabilizer, and 1.5kg of processing aid LPA40.
[0055] The active nano calcium carbonate is prepared by the following steps: 8 kg of calcium hydroxide is added to 80 kg of water, stirred at a speed of 1500 r / min for 15 minutes, 0.05 kg of yttrium oxide is added under stirring, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 10 L / min, the introduction time is 15 seconds, and spray drying is performed; the water is added to 15 kg of dioxane, 0.5 kg of polylactic acid is added, stirred at a temperature of 88° C. for 20 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 125° C. for 8 minutes, cooled to room temperature, and crushed.
[0056] The activated fiber is prepared by the following steps: 8 kg of lignin is added to 25 kg of deionized water and stirred evenly, 1.5 kg of sodium silicate and 1.5 kg of sodium alginate are added thereto under stirring, stirred at 88 ° C for 20 minutes, hydrochloric acid is used to adjust the pH value of the system to 2-3, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 210 ° C.
[0057] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride, activated fiber and graphene oxide into a mixer, stir at 150°C for 20 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, zinc borate, calcium zinc stabilizer and processing aid LPA40 in sequence, continue stirring for 10 min, extrude at 190°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 120°C for 20 minutes, adding active nano calcium carbonate, paraffin, stearic acid, ammonium polyphosphate, and calcium zinc stabilizer in sequence, mixing evenly, extruding at a temperature of 190°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0058] Comparative Example 2 A flame-retardant PVC sleeve comprises an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding.
[0059] The raw materials of the inner tube include: 120kg of polyvinyl chloride, 2kg of chlorinated polyethylene, 30kg of active nano calcium carbonate, 1.5kg of paraffin, 1.5kg of stearic acid, 2kg of ammonium polyphosphate, and 1.5kg of calcium zinc stabilizer.
[0060] The raw materials of the outer tube include: 80kg of polyvinyl chloride, 3kg of activated fiber with a diameter of 0.2mm and a length of 4mm, 15kg of active nano calcium carbonate, 1.5kg of zeolite powder, 1.5kg of magnesium oxide, 1.5kg of paraffin, 1.5kg of polyethylene wax, 1.5kg of stearic acid, 3kg of zinc borate, 2kg of calcium zinc stabilizer, and 1.5kg of processing aid LPA40.
[0061] The active nano calcium carbonate is prepared by the following steps: 8 kg of calcium hydroxide is added to 80 kg of water, stirred at a speed of 1500 r / min for 15 minutes, carbon dioxide gas is introduced into the water under stirring, wherein the gas flow rate is 10 L / min, the introduction time is 15 seconds, and spray drying is performed; added to 15 kg of dioxane, 0.5 kg of polylactic acid is added, stirred at a temperature of 88° C. for 20 minutes, the solvent is removed under reduced pressure, stirring is continued at a temperature of 125° C. for 8 minutes, cooled to room temperature, and crushed.
[0062] The activated fiber is prepared by the following steps: 8 kg of lignin is added to 25 kg of deionized water and stirred evenly, 1.5 kg of sodium silicate, 1.5 kg of sodium alginate and 2 kg of graphene oxide are added thereto under stirring, stirred at 88 ° C for 20 minutes, the pH value of the system is adjusted to 2-3 with hydrochloric acid, the deionized water is removed by rotary evaporation, and melt spinning is performed after drying, and the spinning temperature is 210 ° C.
[0063] The preparation method of the flame-retardant PVC casing comprises the following steps: S1. Add polyvinyl chloride and activated fiber into a mixer, stir at 150°C for 20 min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, zinc borate, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 10 min, extrude at 190°C, and pelletize to obtain an outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at a temperature of 120°C for 20 minutes, adding active nano calcium carbonate, paraffin, stearic acid, ammonium polyphosphate, and calcium zinc stabilizer in sequence, mixing evenly, extruding at a temperature of 190°C, and pelletizing to obtain an inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
[0064] The flame-retardant PVC sleeves obtained in Example 5 and Comparative Examples 1-2 were sampled, and performance tests were performed on each group of samples, as follows: (1) The tensile strength of each group of specimens was measured with reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics"; (2) Determine the flexural strength of each group of samples with reference to GB / T 9341-2008 "Determination of flexural properties of plastics"; (3) The impact strength of each group of samples was measured with reference to GB / T 1043.1-2008 “Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test”; (4) The oxygen index of each group of samples was measured with reference to GB / T 2406.2-2009 “Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test”.
[0065] like Figure 1 and Figure 2 As shown, the tensile strength, bending strength, impact strength and oxygen index of the flame-retardant PVC casing sample obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05). At the same time, during the oxygen index measurement process, it was found that the smoke emission of the flame-retardant PVC casing sample obtained in Example 5 was significantly less than that of Comparative Examples 1-2.
[0066] The applicant believes that the reason for the above results is that the present invention combines graphene oxide in the lignin matrix, and then the activated fiber obtained after spinning not only has good affinity with polyvinyl chloride, but also effectively improves the thermal conductivity of the outer tube on the basis of ensuring the mechanical strength of the product, and cooperates with the metal copper mesh to quickly transfer the heat of the cable to the external environment, so that the heat will not accumulate on the inner tube that is in direct contact with the cable, effectively ensuring the normal operation of the cable. At the same time, polyvinyl chloride and activated fibers are compounded, and the two have high bonding strength. Further combined with active nano-calcium carbonate, not only can they provide good support and excellent thermal conductivity for the casing, but the system has high impact resistance and excellent flame retardant properties. The present invention adds calcium hydroxide into water to form a suspension, and then adds yttrium oxide and treats it with carbon dioxide to form yttrium-doped nano calcium carbonate particles, and then combines polylactic acid on the surface, which can not only significantly increase the dispersibility and stability of calcium carbonate, but also has high interfacial compatibility with polyvinyl chloride substrates, significantly improving the mechanical properties of the material; the active nano calcium carbonate is compounded with the flame retardant, and the synergistic effect is significant, which can not only ensure the impact strength of the material, but also greatly enhance the flame retardant effect and have a significant smoke suppression effect.
[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A flame retardant PVC casing, characterized in that: It comprises: an inner tube, a metal copper mesh wrapped around the outer side of the inner tube, and an outer tube wrapped around the metal copper mesh and the outer side of the inner tube by injection molding; The raw materials of the inner tube include, by mass: 80-150 parts of polyvinyl chloride, 1-3 parts of chlorinated polyethylene, 20-40 parts of active nano calcium carbonate, 1-2 parts of paraffin, 1-2 parts of stearic acid, 1-3 parts of flame retardant, and 1-2 parts of calcium zinc stabilizer; The outer tube raw materials include, by mass: 50-120 parts of polyvinyl chloride, 1-5 parts of activated fiber, 10-20 parts of active nano calcium carbonate, 1-2 parts of zeolite powder, 1-2 parts of magnesium oxide, 1-2 parts of paraffin, 1-2 parts of polyethylene wax, 1-2 parts of stearic acid, 1-5 parts of flame retardant, 1-3 parts of calcium zinc stabilizer, and 1-2 parts of processing aid LPA40.
2. The flame-retardant PVC sleeve according to claim 1, characterized in that: The flame retardant is at least one of zinc borate, zinc stannate, ammonium octamolybdate and ammonium polyphosphate.
3. The flame-retardant PVC sleeve according to claim 1, characterized in that: The active nano calcium carbonate is prepared by the following steps: adding calcium hydroxide to water and stirring for 10-20 minutes, adding yttrium oxide under stirring, introducing carbon dioxide gas into the water under stirring, and spray drying; adding to dioxane, and then adding polylactic acid, stirring at 80-95° C. for 10-30 minutes, removing the solvent under reduced pressure, continuing to stir at 120-130° C. for 5-10 minutes, cooling to room temperature, and crushing.
4. The flame-retardant PVC sleeve according to claim 3, characterized in that: The mass ratio of calcium hydroxide, yttrium oxide and polylactic acid is 5-10:0.01-0.1:0.1-1.
5. The flame-retardant PVC sleeve according to claim 1, characterized in that: The activated fibers have a diameter of 0.1-0.3 mm and a length of 3-5 mm.
6. The flame-retardant PVC casing according to claim 1, characterized in that: The activated fiber is prepared by the following steps: adding lignin to deionized water and stirring evenly, adding sodium silicate, sodium alginate and graphene oxide thereto under stirring, stirring at 80-95° C. for 10-30 minutes, adjusting the pH value of the system to 2-3, rotary drying, and melt spinning.
7. The flame-retardant PVC sleeve according to claim 6, characterized in that: The mass ratio of lignin, sodium silicate, sodium alginate and graphene oxide is 5-10:1-2:1-2:1-3.
8. The flame-retardant PVC casing according to claim 6, characterized in that: The spinning temperature is 200-220°C.
9. A method for preparing the flame-retardant PVC casing according to any one of claims 1 to 8, characterized in that: The steps include: S1. Mix polyvinyl chloride and activated fiber, stir at 100-140°C for 10-30min, add active nano calcium carbonate, zeolite powder, magnesium oxide, paraffin, polyethylene wax, stearic acid, flame retardant, calcium zinc stabilizer, and processing aid LPA40 in sequence, continue stirring for 5-15min, extrude at 180-200°C, and pelletize to obtain outer tube masterbatch; S2, adding polyvinyl chloride and chlorinated polyethylene into a mixer, stirring at 100-140°C for 10-30min, adding active nano calcium carbonate, paraffin, stearic acid, flame retardant, calcium zinc stabilizer in sequence, mixing evenly, extruding at 180-200°C, and pelletizing to obtain inner tube masterbatch; S3. After the inner tube masterbatch is extruded, it is sequentially sizing, pulling and cutting to a fixed length to form an inner tube, the outer wall of the inner tube is sequentially coated with a metal copper mesh, and then the outer tube masterbatch is injection molded to coat the metal copper mesh and the outer side of the inner tube.
Citation Information
Patent Citations
Preparation method of active light calcium carbonate
CN112875739A
Environment-friendly polymer silicon core tube and preparation method thereof
CN117103791A
The method for preparation of hydrogel-based drug delivery system
KR1020170093317A
Silicon-based monobasic or multibasic oxide aerogel material and preparation method therefor
WO2015192731A1
Ring-opening metathesis reactions for preparation of carbon nanotube composites
WO2023275051A1